Petrographical analysis of Warthian fluvioglacial gravels as a tool to trace the source area – a case study from central Poland - Górska-Zabielska, Maria; Wachecka-Kotkowska, Lucyna (Instytut Geologii UAM, 2014)
The petrographical features of the medium- and coarse-grained gravels (4-10 mm and 20-60 mm, respectively) of weathered and fresh (unweathered) deposits indicate, in combination with so-called indicator and statistical erratics, that two glacial lobes joined in the borderland of the Polish Lowlands and Uplands. Lower Palaeozoic limestones become less frequent in the finer gravel fraction, whereas crystalline rocks and flints become more frequent. The petrographical analysis of the coarser gravel fraction indicates that the ice sheet advanced from the NE to NNW (the Widawka lobe) and from the NE to ENE (the Rawka, Pilica and Luciąża lobes). The source areas of the gravel deposited by the Warthian ice sheet were magmatic and sedimentary areas of both the Baltic and the SE Sweden basins.